2003
DOI: 10.1002/jsfa.1318
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of ginger extract in sunflower oil

Abstract: The antioxidant activity of dichloromethane extract from ginger was evaluated during 6 months of storage of refined sunflower oil at 25 and 45°C. Free fatty acid (FFA) content, peroxide value (POV) and iodine value (IV) were used as criteria to assess ginger extract as an antioxidant. After 6 months of storage at 45°C, sunflower oil containing 1600 and 2400 ppm ginger extract showed lower FFA contents (0.083 and 0.080%) and POVs (24.5 and 24.0 meq kg À1 ) than the control sample (FFA contents 0.380%, POV 198.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 13 publications
4
26
0
2
Order By: Relevance
“…During storage the significant overall decrease was reported in mean juiciness score of control and treated spent hen meat sausages. Improvements in juiciness score are in agreement with results of the Zia-ur-Rehman et al, (2003). Decrease in juiciness with progress in storage might be due to moisture loss during aerobic storage of sausages.…”
Section: Resultssupporting
confidence: 86%
“…During storage the significant overall decrease was reported in mean juiciness score of control and treated spent hen meat sausages. Improvements in juiciness score are in agreement with results of the Zia-ur-Rehman et al, (2003). Decrease in juiciness with progress in storage might be due to moisture loss during aerobic storage of sausages.…”
Section: Resultssupporting
confidence: 86%
“…There was no discernible difference (P > 0.05) between the antioxidant potentials of T 2 and T 3 (600 and 800 ppm). Zia-ur-Rehman et al (2003) investigated the impact of ginger extract on the oxidative stability of sunflower oil and reported that the vegetable extract was quite effective for the stabilisation of sunflower oil. Mohdaly et al (2011) studied the antioxidant potential of sesame (Sesamum indiucm) cake extract to prolong the shelf life of sunflower and soybean oils and found that the incorporation of sesame cake extract significantly (P < 0.05) improved the keeping quality of sunflower and soybean oils without having a drastic negative effect on sensory characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Ginger (Zingiber officinale), contains relatively large amounts of volatile oils camphene, alpha-terpineol, p-cineole, zingiberene, and pentadecanoic acid (El-Ghorab et al, 2010) both in the fresh and dried form. Ginger extracts revealed antioxidant activity almost equal to that of synthetic antioxidants such as BHA and BHT (Rehman et al, 2003).…”
Section: Introductionmentioning
confidence: 90%